A Review of Enhancement of Thermal Performance of Flat Plate Solar Collectors through Nanofluid Implementation - Zahraa H. Mohammed Ali; Adnan M. Hussien (Advances in Mechanical and Materials Engineering, 2023)
Nanofluids have found widespread practical applications in heat transfer, including cooling oils for diverse uses like automobile radiators, solar and nuclear power systems, biomedical devices, ventilation, heating, air conditioning, refrigeration, engine cooling, and transformers. Extensive scientific studies have investigated the impact of exotic fluids when combined with traditional heat transfer fluids, revealing that this combination enhances heat transfer performance beyond that of conventional working fluids. Collectively, these studies demonstrate the impressive heat transfer abilities of nanofluids. To optimize the efficiency of flat plate solar collectors, a comprehensive approach integrating theory and experimentation is essential. The results of such research highlight that increasing both the mass flow rate and concentration of nanofluids can lead to significant efficiency improvements, with potential enhancements ranging from 20% to 85%.